THE CHANGING CLINICAL PERFORMANCE OF DENGUE VIRUS INFECTION IN THE YEAR 2009 - Soegijanto, Soegeng; Susilowati, Helen; Mulyanto, Kris Cahyo; Hendrianto, Eryk; Yamanaka, Atushi (Indonesian Journal of Tropical and Infectious Disease, 2012)
Background: Dengue (DEN) virus, the most important arthropod-borne human pathogen, represents a serious public healthÂ threat. DEN virus is transmitted to humans by the bite of the domestic mosquito, Aedes aegypti, and circulates in nature as four distinctÂ serological types DEN-1 to 4).Â The aim of Study: To identify Dengue Virus Serotype I which showed mild clinical performance in fiveyears before and afterward showed severe clinical performance.Â Material and Method: Prospective and analytic observational studyÂ had been done in Dr. Soetomo Hospital and the ethical clearance was conduct on January 01, 2009. The population of this researchÂ is all cases of dengue virus infection. Diagnosis were done based on WHO 1997. All of these cases were examined for IgM & IgG antiÂ Dengue Virus and then were followed by PCR examination to identify Dengue Virus serotype.Â Result and Discussion: DEN 2 wasÂ predominant virus serotype with produced a spectrum clinical illness from asymptomatic, mild illness to classic dengue fever (DF) to theÂ most severe form of illness (DHF). But DEN 1 usually showed mild illness. Helen at al (2009â2010) epidemiologic study of Dengue VirusÂ Infection in Health Centre Surabaya and Mother and Child Health Soerya Sidoarjo found many cases of Dengue Hemorrhagic Feverwere caused by DEN 1 Genotype IV. Amor (2009) study in Dr. Soetomo Hospital found DEN 1 showed severe clinical performance ofÂ primary Dengue Virus Infection as Dengue Shock Syndrome two cases and one unusual case.Conclusion: The epidemiologic study ofÂ Dengue Virus Infection in Surabaya and Sidoarjo; in the year 2009 found changing predominant Dengue Virus Serotype from DengueÂ Virus II to Dengue Virus 1 Genotype IV which showed a severe clinical performance coincident with primary infection.